Space closure loops performance - Coimbra, Maria Elisa Rodrigues (2010)
The authors executed an experimental study in order to evaluate the mechanical properties of three different types of orthodontic loops in terms of: discharged force and torque incorporated during activation. Seventy-five closing loops divided into three groups (helicoidal reverse, teardrop and T reverse). The one way Anova test with the Tukey test as post hoc was used to compare means. The confidence interval was 99% (p< 0,01) and 95% (p < 0,05). The teardrop spring released significantly more force than the reverse helicoid and the reverse T for all activation levels. The last one incorporated more torque than the other two. But for all the three loops analyzed, the values were too low to be considered regarding torque incorporation.